2017
DOI: 10.18632/oncotarget.20574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymphocyte-to-monocyte ratio among Asian lung cancer patients: a systematic review and meta-analysis

Abstract: PurposeNumerous studies have reported the prognostic significance of lymphocyte-to-monocyte ratio (LMR) in malignancies, but its prognostic value among lung cancer remains controversial. This meta-analysis aimed to explore the prognostic significance of LMR in lung cancer patients.ResultsEight studies including 3954 patients were included in this meta-analysis. Pooled results indicated that low LMR was significantly associated with poorer progression-free survival (hazard ratio (HR): 1.431, 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…Four, the optimal cutoff values of the NLR, PLR, and LMR in our study were 2.12, 92.9, and 4.57, respectively. In previous studies, their critical values ranged from 2.5 to 5, 106 to 300, and 2.62 to 4.56, respectively; therefore, the critical values in the current study may only be appropriate to the population of our center. If physicians from other medical centers attempt to apply this prognostic scoring system, we suggest that they perform their own analysis to obtain the local cutoff values that are appropriate to the specific patient population.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Four, the optimal cutoff values of the NLR, PLR, and LMR in our study were 2.12, 92.9, and 4.57, respectively. In previous studies, their critical values ranged from 2.5 to 5, 106 to 300, and 2.62 to 4.56, respectively; therefore, the critical values in the current study may only be appropriate to the population of our center. If physicians from other medical centers attempt to apply this prognostic scoring system, we suggest that they perform their own analysis to obtain the local cutoff values that are appropriate to the specific patient population.…”
Section: Discussionmentioning
confidence: 84%
“…The association between blood cell counts or their ratios with lung cancer prognosis has been explored . Yin et al conducted a meta‐analysis including 2734 patients from 14 studies and reported that a high NLR was a predictor of poor OS in lung cancer (HR 1.192, 95% CI 1.061–1.399; P heterogeneity = 0.003) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lymphocyte-to-monocyte ratio (LMR) has been reported to reflect host immunity in various malignancies. [11][12][13][14] Peripheral lymphocytes represent tumour-related lymphocytes, while peripheral monocytes represent TAMs. Therefore, low and high LMRs indicate weak and strong immune responses against tumours, respectively.…”
Section: Introductionmentioning
confidence: 99%